Organic zinc and copper supplementation on antioxidant protective mechanism and their correlation with sperm functional characteristics in goats. (15th February 2018) - Narasimhaiah, M; Arunachalam, A; Sellappan, S; Mayasula, VK; Guvvala, PR; Ghosh, SK; Chandra, V; Ghosh, J; Kumar, H
Contents: Trace minerals feeding had significant effects on sperm production and fertility with better absorption and proper utilization within the body for optimum reproductive function. Several studies have shown that more influenced trace elements in the diets of animals are copper (Cu) and zinc (Zn). Bucks showing deficiency of this mineral might affect the quality of semen production which in turn would affect the fertility. This experiment was thus designed to test the effects of organic Cu and Zn supplementation on antioxidants enzyme activities and sperm functional attributes in fresh semen of bucks. Forty bucks ( n = 40, Aged 5 months) were assigned to ten groups of four animals in each group, supplemented (for a period of 8 months) with different levels of organic Zn: 20 mg (T2), 40 mg (T3) and 60 mg (T4), organic Cu: 12.5 mg (T5), 25 mg (T6), 37.5 mg (T7) and combined organic Zn and Cu: 20 + 12.5 mg (T8), 40 + 25 mg (T9), 60 + 37.5 mg (T10), respectively, per kg dry matter and no additional mineral diet (control; T1). One hundred and sixty semen samples were collected through electro‐ejaculator and analysed for sperm quantity, quality, acrosome intactness and plasma membrane integrity and correlated with the catalase, superoxide dismutase, glutathione peroxidase and glutathione reductase enzyme activities in seminal plasma. The results indicated organic Cu and zinc supplemented bucks produced more sperm cells, had higher sperm concentrations, maintained higher ( p < .01) sperm livability, plasma membrane and acrosome integrities, more motility and velocity. The increased antioxidant enzyme activities, reduced oxidative stress and lowered lipid peroxidation were positively correlated ( p < .05) with the sperm functional attributes. In conclusion, organic Cu and Zn supplement to male goats showed protective roles against oxidative damage and maintained better fresh semen characteristics.